2018
DOI: 10.1002/joc.5470
|View full text |Cite
|
Sign up to set email alerts
|

Inter‐annual and inter‐decadal variability of early‐ and late‐summer precipitation over northeast China and their background circulation

Abstract: Using precipitation data from weather stations in China and reanalysis data from National Centers for Environmental Prediction/National Center for Atmospheric Research (NCEP/NCAR), the inter‐annual and inter‐decadal variability of early‐summer (May–June) and late‐summer (July–August) precipitation (hereinafter referred to as MJP and JAP, respectively) over northeast China (NEC) and their background circulation during 1951–2016 were analysed. The following new findings have been highlighted: (a) There are signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 20 publications
(20 reference statements)
2
16
0
Order By: Relevance
“…These results are consistent with that of previous studies, which have proposed that NECR is affected mainly by the East Asian subtropical monsoon system (for example, the WNPAC and NEC southerly winds), and the westerly circulation system (such as the NEC cold vortex) in late summer (Fang et al 2018;Shen et al 2011;Zhao et al 2018). Among them, the WNPAC is the dominant factor contributing to the NECR variability by modulating the northward transport of water vapor from the ocean.…”
Section: Simultaneous Sstas and Atmospheric Circulation Anomalies Associated With The Interannual Variation Of Late Summer Necrsupporting
confidence: 93%
“…These results are consistent with that of previous studies, which have proposed that NECR is affected mainly by the East Asian subtropical monsoon system (for example, the WNPAC and NEC southerly winds), and the westerly circulation system (such as the NEC cold vortex) in late summer (Fang et al 2018;Shen et al 2011;Zhao et al 2018). Among them, the WNPAC is the dominant factor contributing to the NECR variability by modulating the northward transport of water vapor from the ocean.…”
Section: Simultaneous Sstas and Atmospheric Circulation Anomalies Associated With The Interannual Variation Of Late Summer Necrsupporting
confidence: 93%
“…On the interdecadal timescale, summer precipitation is observed to significantly decrease since the end of the 1970s (Ding et al, ; Liu et al, ; Sun & Wang, ), which might be partially linked to the abrupt decrease of preceding winter and spring snows over the Tibetan Plateau (Ding et al, ). In addition, the summer precipitation over NEC also experienced an interdecadal decrease after the end of the 1990s (Zhao et al, ). Similar to changes in precipitation, the summer SAT over NEC experienced a shift toward a warm phase in the early 1990s (Chen & Lu, ).…”
Section: Introductionmentioning
confidence: 99%
“…Lu et al (2020) analyzed the spring precipitation levels in the NEC region, and revealed the physical mechanism in which the SSTs of the tropical North Atlantic and the northwestern Pacific Ocean influenced the low value systems over the NEC region during the spring seasons with the characteristics of interannual variability. In addition, other meaningful research investigations have carried out from other relevant aspects (Fang et al, 2017a;Fang et al, 2017b;Zhao et al, 2018;Zhao et al, 2019).…”
Section: Introductionmentioning
confidence: 99%